Esophageal cancer associated with a sarcoid-like reaction and systemic sarcoidosis in lymph nodes: supportive findings of [18F]-fluorodeoxyglucose positron emission tomography–computed tomography during neoadjuvant therapy - Takayoshi Kishino; Keiichi Okano; Yasuhisa Ando; Hironobu Suto; Eisuke Asano; Minoru Oshima; Masao Fujiwara; Hisashi Usuki; Hideki Kobara; Tsutomu Masaki; Emi Ibuki; Yoshio Kushida; et al. (Surgical Case Reports)
Abstract Background In patients with esophageal cancer, differentiation between lymph node metastasis and lymphadenopathies from sarcoidosis or sarcoid-like reactions of lymph nodes is clinically important. Herein, we report two esophageal cancer cases with lymph node involvement of sarcoid-like reaction or sarcoidosis. Case presentation One patient received chemotherapy and the other chemoradiotherapy as initial treatments. In both cases, [18F]-fluorodeoxyglucose positron emission tomography–computed tomography (FDG-PET/CT) was performed before and after chemo(radio)therapy. After the treatment, FDG uptake was not detected in the primary tumor, but it was slightly reduced in the hilar and mediastinal lymph nodes in both cases. These non-identical responses to chemo(radio)therapy suggest the presence of sarcoid-like reaction of lymph nodes associated with squamous cell carcinoma of the esophagus. Curative surgical resection was performed as treatment. Conclusions These FDG-PET/CT findings may be helpful to distinguish between metastasis and sarcoidosis-associated lymphadenopathy in esophageal cancer.